Towards a Blockchain-based Data Recorder for Small Drones - Böhm, Harald; Distler, Tobias; Kapitza, Rüdiger (2nd Workshop on Resilient Operations – Byzantine Fault Tolerance and State-Machine Replication (ROBUST '25), 2025)
Building a reliable and tamper-resistant flight data recorder for small drones is a task that comes with unprecedented requirements in terms of robustness, resource efficiency and weight. In this paper, we report on our ongoing efforts to solve the associated problems by developing a solution that records all relevant information (e.g., positional data) in an on-board permissioned blockchain. The proposed system, through physical replication, aims to achieve data persistence despite catastrophic events such as a drone crash. All recorded data is replicated across three nodes and kept consistent by a Byzantine fault-tolerant (BFT) protocol. Leveraging the specific properties of our hardware setting, this protocol does not implement full-fledged BFT consensus, but instead relies on a tailored reliable-broadcast mechanism optimized for memory efficienc